Outpacing Economic Growth and the Competitiveness of the Bulgarian Economy (Macroeconomic Perspective) (UNWE Yearbook, 2008)
The objective of the study is to examine the outpacing economic growth and the competitiveness of the Bulgarian economy in the beginning of the 21st century. The first part of the study proves that in 2001-2006 the growth of GDP approximated 60% of the possible and necessary rate. In the years of the market transformation (1989-2006) Bulgaria was one of the slowest developing economies in CEE and this fact is unlikely to ensure its meeting the strategic goals of development by 2020. The GDP growth in the next decades should exceed by 2,5 -3.5 times the anticipated high rates of growth of the EU. Bulgaria needs not only an accelerated development but an outpacing development since any type of outpacing development is accelerated but not every type of accelerated development means outpacing.The second part of the study puts forward a system of economic competitiveness indexes. 14 result-oriented (direct) and 9 factor-oriented (indirect) indexes are recommended. All of them confirm that Bulgaria is the least or one of the least competitive economies among the EU member countries. The findings also bear out a high correlation ratio between the direct and the indirect indicators. Some indexes have marked a slow improvement but most of them suggest stagnation of competitiveness. Decades will be needed to catch up with average competitiveness indexes in the EU, which is an even higher figure compared to what is needed to catch up with the overall economic growth measured by GDP per person.